Altruism as Reparation of Mismatch or Disruption in the Self. Issue 7 (3rd October 2017) - Harrison, Alexandra Murray
ABSTRACT: After giving a brief summary of the scientific literature on altruism and empathy—a capacity necessary for altruism—I focus on a scientific paradigm, the face-to-face still face, and what insights it might offer psychoanalysts in their understanding of altruism. The face-to-face still face provides data about the communication of intentions and affect between infant and caregiver and demonstrates the procedure of mutual regulation, the foundation of self-regulation and empathy. Both infant and caregiver are highly motivated to repair mismatches or disruptions in the affective connection between them and this desire to repair disruptions can also be recognized in adulthood—both in relationships between individuals and within an individual in terms of disconnections with the self. The subjective experience of the altruist may derive from this domain of human experience—the repair of disruption. I thus suggest that altruism is not merely sublimation of inner conflict, but it is an adaptive, evolutionarily beneficial, attitude and behavior that is growth enhancing in that it expands the individual's repertoire for repairing mismatches within the self.